The Urgency of Administrative Law in Light of Ius Constituendum Regarding the Role of Village Heads - Rahmat, Diding; Sudarto, Sudarto; Sarip, Sarip; Sujono, Sujono; Aziz, Muhammad Faiz (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
This article delves into the crucial aspects of the Constitutional Court of the Republic of Indonesia's decision, focusing on the emergency state of administrative law concerning open legal policy decisions referred back to legislators, particularly regarding the tenure of village heads. The study employs a conceptual and legal approach, centering on the Constitutional Court Decision No.15/PUU-XI/2023 concerning the village head's position. This represents an open legal policy for law framers, paving the way for the political prevention of Pilkades (village head elections) money politics. Law No. 6 of 2014, which is under consideration for revision, lacks explicit measures against money politics. The methodology adopted is normative legal research that integrates legal theory with legislation. The findings indicate that open legal policy rulings necessitate immediate action by law framers, signaling administrative law urgency. The rationale is that law framers must react to that decision, and revising the law does not necessarily require inclusion in the National Legislation Program (Prolegnas). Decision on open legal policies must be administratively executed by law framers, including the issuance of Government Regulation in Lieu of Law (Perpu), which subsequently require legislative approval to become law. In essence, the decision of the Constitutional Court carries a moral and ethical coercive force, achieved by transforming ius constitutum into ius constituendum.